The Nouvelle Droite in Portugal: a new strategy for the Portuguese radical right – between the authoritarian regime and the transition to democracy - Marchi, R. (Patterns of Prejudice, 2016)
Marchi examines how the French Nouvelle Droite (ND) was introduced into Portugal at the end of the Salazarist regime and during the transition to democracy. The relevance of the Portuguese case lies in the fact that the early diffusion of the ND in Europe coincided with the profound crisis of the radical right in Portugal as it faced the liberalization of the authoritarian regime and repression during the revolutionary transition. For that reason the far right in Portugal, in comparative terms, can be seen to have been subject to historical constraints quite different from those in Spain and other Western European democracies. Marchi describes the groups on the Portuguese radical right, and certain figures who were inspired by the ND and disseminated its ideas in Portugal. His analysis of their main publications, their statements and the media campaign to promote the ND from the end of the 1960s to the beginning of the 1980s highlights the different reasons for and ways in which Portuguese radicals engaged and dealt with the ND. Marchi also looks at the reactions of the national right-wing milieu to the spread of ND ideas. As part of his paper’s contribution to comparative studies on the transnational radical right, it also provides new evidence, derived from the Portuguese case, of the way in which one of the most important schools of right-wing thought at the end of the twentieth century has influenced extreme-right milieux all over Europe. In light of Tamir Bar-On's analysis of the ND's cultural and pan-European impact, the findings presented here confirm its transnational character while drawing on this and other cases from southern Europe to question the French movement's long-term effectiveness in reorienting the culture of the right-wing milieu.